The Relationship Between Leg Muscle Strength and 100-Meter Running Speed in High School Athletes - Dahri, Suci Yati; Prawibowo, Muhammad; Mardiansyah, Muhammad Alfin; Alhafi, Muhammad Iqbal; Saputra, Ilpan (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2025)
This study aims to determine how strong the leg muscle strength is with the 100-meter running speed in class X students at SMA Negeri 1 Kepenuhan Hulu. The hypothesis in this study is "There is a relationship between leg muscle strength and 100-meter running speed in class X students at SMA Negeri 1 Kepenuhan Hulu". The method used is an experimental method, with the steps "Pre Test (X1), Treatment (T), and Post Test (X2). The sample used for this study consisted of 10 students of Grade X at SMA Negeri 3 Kepenuhan Hulu. Participants were selected using purposive sampling based on their active involvement in school athletics. Muscle strength was measured using a leg dynamometer, while sprint speed was recorded using a digital stopwatch. The findings revealed a significant negative correlation (r = -0.68, p < 0.01) between leg muscle strength and 100-meter sprint time, indicating that greater muscle strength is associated with faster sprint performance. The data in this study were the results of the 100-meter run performed by students. Data analysis was carried out using a percentage statistical formula. The data can prove that there is a relationship between leg muscle strength and 100-meter sprint speed in grade X students at SMA Negeri 1 Kepenuhan Hulu.